A hat full of sky - Pratchett, Terry (Pratchett, Terry. Tiffany Aching series., 2015)
Tiffany Aching, a young witch-in-training, learns about magic and responsibility as she battles a disembodied monster with the assistance of the six-inch-high Wee Free Men and Mistress Weatherwax, the greatest witch in the world.